Alcaligenaceae and Chromatiaceae as reliable bioindicators present in palm oil mill effluent final discharge treated by different biotreatment processes. (December 2018) - Mohd-Nor, Diana; Ramli, Norhayati; Sharuddin, Siti Suhailah; Hassan, Mohd Ali; Mustapha, Nurul Asyifah; Amran, Afzufira; Sakai, Kenji; Shirai, Yoshihito; Maeda, Toshinari
Highlights: Alcaligenaceae and Chromatiaceae were detected in different POME final discharges. These bioindicators were reliable despite the different treatment processes used. These bioindicators were strongly correlated with BOD5 . These bioindicators could be used to detect the contamination by final discharge. Abstract: This study was undertaken to confirm the reliability of the proposed potential bioindicators, Alcaligenaceae and Chromatiaceae to specifically indicate contamination in river water by palm oil mill effluent (POME) final discharge. The use of bioindicators could assist in determining the specific cause of contamination in water bodies. Alcaligenaceae and Chromatiaceae were shown by a previous study to be present in river water contaminated with the final discharge from the treatment of POME. In the present study, the compositions of the bacterial communities in the POME final discharge obtained from four different palm oil mills which used different biotreatments of POME were elucidated using high-throughput MiSeq. The four POME final discharges studied showed different species richness and evenness among them. However, the bacterial community compositions in the different final discharges exhibited almost similar patterns in that the phylum Proteobacteria was dominant in all the samples. The proposed bioindicators, the Alcaligenaceae and Chromatiaceae families, were found to be present in all the four final discharges despite the different characteristics of the mills and the different biotreatment processes used by them. These bioindicators were also strongly and positively correlated with the biochemical oxygen demand (BOD5 ) concentration. This makes them reliable bacterial indicators to detect the presence of POME final discharge in river water.